2013
DOI: 10.1111/jpn.12009
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme effects on extruded diets for dogs with soybean meal as a substitute for poultry by‐product meal

Abstract: Summary The effects of exogenous enzymes supplementation on kibble diets for dogs formulated with soybean meal (SBM) as a substitute for poultry by‐product meal (PM) was investigated on nutrient digestibility, fermentation products formation, post‐prandial urea response and selected faecal bacteria counts. Two kibble diets with similar compositions were used in two trials: PM‐based diet (28.9% of PM; soybean hulls as a fibre source) and SBM‐based diet (29.9% of SBM). In experiment 1, the SBM diet was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
2
23
2
Order By: Relevance
“…The substitution of PBM by both SPC products and GM did not reduce faecal pH or alter faecal lactate or ammonia, which is evidence that no increase in organic matter fermentation occurred in the colon. The addition of soya bean meal to dog foods is associated with higher carbohydrate fermentation in the colon, resulting in increased faecal production, lower faecal pH and ammonia content, and higher faecal lactate and short‐chain fatty acids (Maria et al., ; Tortola et al., ). These properties are the result of fermentation of the oligosaccharides and soluble non‐starch polysaccharides present in the soya bean meal by the gut bacteria (Bednar et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The substitution of PBM by both SPC products and GM did not reduce faecal pH or alter faecal lactate or ammonia, which is evidence that no increase in organic matter fermentation occurred in the colon. The addition of soya bean meal to dog foods is associated with higher carbohydrate fermentation in the colon, resulting in increased faecal production, lower faecal pH and ammonia content, and higher faecal lactate and short‐chain fatty acids (Maria et al., ; Tortola et al., ). These properties are the result of fermentation of the oligosaccharides and soluble non‐starch polysaccharides present in the soya bean meal by the gut bacteria (Bednar et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that this ingredient has good digestibility (Carciofi et al, 2006;Clapper et al, 2001;Maria et al, 2017). Studies have been published describing attempts to increase the nutritional value of soybean meal, especially with the addition of enzymes to diets with good results on digestibility (Félix et al, 2012) and postprandial protein utilization (Tortola et al, 2013). Other soya bean co-products have been studied for dog diets, such as full fat micronized soya bean, which has nutrient digestibility similar or superior to the PBM (Carciofi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve one-year-old Beagle dogs, six males and six females, (11.3 ± 1.1 kg of body weight, BW) participated in the trial. The sample size was calculated using power analysis, assuming a power of 95% and a p-value of 0.05 from data previously published by Wedekind and Lowry (1998) [4], and Tortola et al [14], which evaluated Zn sources for dog food supplementation and addition of exogenous enzymes to enhance nutrient digestibility, respectively. All dogs were subjected to a clinical examination to check the suitability to participate in the trial.…”
Section: Animals and Managementmentioning
confidence: 99%
“…It is important to remember that the scale used in this study is inverted to express the same score. In another study the inclusion of different dosages of enzymes blend (proteases, cellulases, pectinases, phytases, betaglucanases, xylanase) did not influence production and fecal quality of dogs fed diets with soybean meal (TORTOLA et al, 2013). Cowieson et al (2006) observed that some exogenous enzymes might increase the excretion of endogenous material from the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%